Serial cranial ultrasonography or early MRI for detecting preterm brain injury?. Issue 4 (30th January 2015) - Plaisier, Annemarie; Raets, Marlou M A; Ecury-Goossen, Ginette M; Govaert, Paul; Feijen-Roon, Monique; Reiss, Irwin K M; Smit, Liesbeth S; Lequin, Maarten H; Dudink, Jeroen
Abstract : Objective: To investigate detection ability and feasibility of serial cranial ultrasonography (CUS) and early MRI in preterm brain injury. Design: Prospective cohort study. Setting: Level III neonatal intensive care unit. Patients: 307 infants, born below 29 weeks of gestation. Methods: Serial CUS and MRI were performed according to standard clinical protocol. In case of instability, MRI was postponed or cancelled. Brain images were assessed by independent experts and compared between modalities. Main outcome measures: Presence of preterm brain injury on either CUS or MRI and discrepant imaging findings on CUS and MRI. Results: Serial CUS was performed in all infants; early MRI was often postponed (n=59) or cancelled (n=126). Injury was found in 146 infants (47.6%). Clinical characteristics differed significantly between groups that were subdivided according to timing of MRI. 61 discrepant imaging findings were found. MRI was superior in identifying cerebellar haemorrhage; CUS in detection of acute intraventricular haemorrhage, perforator stroke and cerebral sinovenous thrombosis. Conclusions: Advanced serial CUS seems highly effective in diagnosing preterm brain injury, but may miss cerebellar abnormalities. Although MRI does identify these lesions, feasibility is limited. Improved safety, better availability and tailored procedures are essential for MRI to increase its value in clinical care.